A Universidade do Porto e a formação inicial de professores = Initial teacher training in University of Porto - Santos, Paulo Jorge (2016)
Initial teacher training programmes are faced with resistance at several levels from classical universities which hinders their effective implementation. This paper intends to analyse the case of the University of Porto. We contend that, although some faculties have included initial teacher training as an institutional purpose, the obstacles to its affirmation create a situation we can call exclusionary tolerance. Finally, several of its more vulnerable areas are identified that objectively hinder the development of higher quality teacher training projects, some of which can also be found in other institutions that train future teachers.